Achievement and maintenance of therapeutic response to brodalumab in patients with moderate‐to‐severe plaque psoriasis: An Italian, observational, retrospective and prospective study (BRIGHT study) - Paolo Dapavo; Gabriella Fabbrocini; Elena Campione; Claudia Giofrè; Anna Balato; Concetta Potenza; Stefano Dastoli; Piergiorgio Malagoli; Annamaria Offidani; Federico Bardazzi; Ketty Peris; Paolo Pella; et al. (Wiley, 2023)
Abstract Background Brodalumab, a fully human anti‐interleukin (IL)‐17 monoclonal antibody that blocks IL‐17RA, is approved in Europe for the treatment of adult patients with moderate‐to‐severe plaque psoriasis who are candidates for systemic treatment. Objectives This study evaluated the achievement and maintenance of therapeutic response for 1 year in psoriasis patients treated with brodalumab in the Italian clinical practice. Methods Real‐world, multicenter, observational, retrospective and prospective study. The retrospective phase ranged from enrolment visit to initiation of brodalumab (12 ± 4 weeks before). The prospective phase ranged from enrolment to a routine follow‐up visit set after 52 ± 4 weeks. Results One hundred eighty‐four patients were eligible and 164 completed the observation period (median 11.9 months; Q1-Q3: 11.4-12.3). At enrolment, the mean duration of disease was 13.9 years (standard deviation; 13.3), 94% of patients (N = 172) had ≥1 clinical manifestation of psoriasis, mainly erythema and itching, and 95.6% had received ≥1 antipsoriatic treatment before brodalumab. Patients who reached an absolute Psoriasis Area and Severity Index (PASI) score ≤3 at week 12 and maintained it ≤3 through week 52 were 97 (64.7%). At week 12, 72.7% of patients achieved PASI 75, 54.5% PASI 90 and 42.0% PASI 100. At Week 52, 92.9% of patients achieved PASI 75, 84.4% PASI 90 and 61.7% PASI 100. A static Physician's Global Assessment (sPGA) score = 0 was obtained by 55.0% of patients after 12 weeks of brodalumab and by 77.0% after 52 weeks. A Dermatology Life Quality Index ≤1 was reported by 71.9% of patients after 12 weeks and by 89.9% after 52 weeks of treatment. No significant outcome differences were shown among patient subgroups defined by previous antipsoriatic treatments (none, systemic other than biologics or biologic) at either brodalumab initiation or any of the subsequent study visits. Conclusions In this real‐world setting, brodalumab was rapidly effective on skin lesions and quality of life both in biologic‐naïve and biologic‐experienced moderate‐to‐severe psoriasis patients, with a favourable safety profile.